Anti-colorectal cancer effects of IRX4 and sensitivity studies to oxaliplatin - Jia, Mei; Kong, Dexian; Fan, Jiaxu; Heng, Bingqian; Zhao, Jian; Li, Binghui; Liu, Shuang; Kong, Peng; Liu, Yabin (Frontiers in Immunology, 2026)
IntroductionColorectal cancer (CRC) remains one of the most lethal malignancies globally. Chemoresistance or reduced chemosensitivity is a key factor contributing to treatment failure in CRC, particularly in patients with advanced-stage disease. Iroquois homeobox protein 4 (IRX4), a transcription factor expressed in multiple tissues, has been demonstrated to be implicated in the progression of many cancers. Based on this background, IRX4 identified through Illumina Infinium 935K methylation chip analysis was chosen to explore its potential role in CRC.MethodsFollowing initial screening via the Illumina Infinium 935K methylation chip, we further confirmed the hypermethylation of IRX4 in CRC tissues using pyrosequencing technology. The expression levels of IRX4 were determined by immunofluorescence (IF) staining, reverse transcription-quantitative polymerase chain reaction (RT-qPCR), and western blot (WB) assays. In vitro cell experiments evaluated the effects of IRX4 overexpression on the proliferation, invasion, migration, and apoptosis of CRC cells, as well as its impact on the chemosensitivity to oxaliplatin (OXA). Mechanistically, after IRX4 overexpression, the phosphorylation level of epidermal growth factor receptor (EGFR) in CRC cells was detected. Luciferase reporter gene assays and immunofluorescence staining were used to investigate the effects of IRX4 overexpression on the activation of the nuclear factor-κB (NF-κB) pathway and the nuclear translocation of the p65 subunit.ResultsIRX4 was downregulated in CRC tissues and cell lines, and its expression was negatively correlated with tumor invasion depth and poor prognosis. In vitro experiments demonstrated that the overexpression of IRX4 inhibited CRC cell proliferation, migration, and invasion and promoted apoptosis. Moreover, IRX4 overexpression enhanced the chemosensitivity of CRC cells to OXA. Mechanistically, IRX4 overexpression significantly inhibited the TNF-α-induced NF-κB transcriptional activity and suppressed the nuclear translocation of NF-κB p65 in CRC cells. Furthermore, combined treatment with OXA and IRX4 overexpression significantly reduced the levels of EGFR and the phosphorylationlevels of EGFR downstream signaling molecules.ConclusionThese findings suggest that IRX4 may be a prognostic biomarker and therapeutic target in CRC. Moreover, IRX4 might regulate CRC progression and chemosensitivity by inhibiting the NF-κB /EGFR pathway, suggesting its potential as a therapeutic target to improve chemotherapeutic efficacy in CRC.